Private donations, government grants, commercial activities, and fundraising: Cointegration and causality for NGOs in international development cooperation - Dierk Herzer; Peter Nunnenkamp (Kiel Institute for the World Economy (IfW), 2012)
NGOs could help scale up foreign aid efforts by mobilizing private donations. However, fundraising activities do not necessarily result in higher donations, and substitution effects between different sources of revenue may diminish the overall pool of NGOs' resources. This paper examines the determinants of private donations to US-based NGOs engaged in international development cooperation. We employ panel cointegration and causality techniques to analyze the interactions between private donations, government grants, commercial revenues and fundraising expenditures. According to our results, a marginal dollar spent on fundraising yields almost five dollars in new donations in the long run. Government grants crowd in private donations in the long run, whereas commercial revenues crowd out donations in the long run. Moreover, our panel vector error correction model reveals complex short-run dynamics.
Keywords: L31; F35; C23; 330; non-governmental organizations; development cooperation; private donations; panel cointegration; Entwicklungsorganisation; Nichtregierungsorganisation; Spendensammlung; Schätzung; USA